Studi Pengelolaan Sampah Berbasis Komunitas pada Kawasan Permukiman Perkotaan di Yogyakarta - Amos Setiadi (Jurnal Wilayah dan Lingkungan, 2015)
Facilitation and stimulation on the environmentally friendly waste management with the Triple-R community-based pattern deal with the problems of limited infrastructure and the lack of incentive and disincentive mechanisms. The waste management organized by the communities actually has developed even though the scope and scale of service remain low. This research applies descriptive and qualitative approaches in nature by using both primary and secondary data collection. The data analysis refers to the relevant waste regulations. The concluding inferences are drawn deductively. The results show that the participatory approach implementation is useful to enabling the local community in conducting self-identification, analysis, and mapping of the actual problems, potentials, threats, and obstacles related to waste management; hence, they could find the appropriate solutions.In fact, they are able to conduct self-organizing practice through collective actions necessary to waste problem solving, which have already been manifested in their higher awareness on responding the waste problems for the sake of mutual interests.